Analysis of 10 km swimming performance of elite male and female open-water swimmers - Vogt, P.; Rüst, C. A.; Rosemann, T. J.; Knechtle, B. (SpringerPlus, 2013)
This study investigated trends in performance and sex difference in swimming speed of elite open-water swimmers at FINA 10 km competitions (i.e. World Cup races, European Championships, World Championships and Olympic Games). Swimming speed and sex difference in swimming speed of the fastest and the top ten women and men per event competing at 10 km open-water races between 2008 and 2012 were analysed using single and multi-level regression analyses. A total of 2,591 swimmers (i.e. 1,120 women and 1,471 men) finished 47 races. Swimming speed of the fastest women (1.35 ± 0.9 m/s) and men (1.45 ± 0.10 m/s) showed no changes across years. The mean sex difference in swimming speed for the fastest swimmers was 6.8 ± 2.5%. Swimming speed of the top ten female swimmers per event was 1.34 ± 0.09 m/s and remained stable across the years. The top ten male swimmers per event showed a significant decrease in swimming speed over time, even though swimming speed in the first race (i.e. January 2008, 1.40 ± 0.0 m/s) was slower than the swimming speed in the last race (i.e. October 2012, 1.50 ± 0.0 m/s) (P < 0.05). To summarize, swimming performances remained stable for the fastest elite open-water swimmers at 10 km FINA competitions between 2008 and 2012, while performances of the top ten men tended to decrease. The sex difference in swimming speed in elite ultra-swimmers (~7%) appeared smaller compared to other ultra-distance disciplines such as running. Further studies should examine how body shape and physiology of elite open-water ultra-distance swimmers influence performances.